An Overview of the Interpretive Framework of Mutual Funds in India (International Journal of Scientific Research in Science and Technology, 2024)
Mutual funds are financial institutions that specialize in collecting surplus income from customers and channeling it closer toward areas that require immediate funds. These financial companies employ their assets to offer their clients the benefits of little risk, steady returns, convenient liquidity, and enhanced value when invested through diversification and skilled management. Mutual funds work as financial mediators, providing a quick and effective way to connect savings and investments. Effectively managed mutual funds provide a mutually advantageous partnership. By offering shares in the expansion of businesses, they make a valuable contribution to the financial community and also have a positive impact on the stock marketplaces. The funds may successfully turn possibilities into profitable returns for consumers by skillfully blending prudence with aggressiveness and evaluation with intuition.